Educational Value of Indonesian Feminism in Kitab Sarinah: Nilai Pendidikan Feminisme Indonesia dalam Buku Sarinah - Nyoman Suwarta; Mochammad Nur Arifin; Edi Dwi Riantiarno; Andriyanto Andriyanto (Academia Open, 2022)
The educational value of Indonesian Feminism is contained in the book, this research seeks to explore the value and social identity. The analysis uses Educational Psychology and Feminism approaches. The qualitative method is used through literature review and text interpretation of Sarinah's book. The research instrument used human instrument. Based on the results of the analysis, the learning process of feminism education in Sarinah's book includes three phases of human evolution, the initial phase, women occupy a low position in life, in the second evolutionary phase, women occupy the highest position in life, and in the third evolutionary phase, women again occupy a low position in life. There are important factors that contribute to the success of students in a learning process, these factors include internal and external factors. Internal factors: Health, Intelligence and talent, Interest and motivation, and Learning style. External factors: Family/parents, School/teachers, Community/environment, Role of family/parents. Highlights: The research explores the educational value of Indonesian Feminism by analyzing Sarinah's book through the lenses of Educational Psychology and Feminism. The learning process of feminism education in Sarinah's book is depicted through three phases of human evolution, reflecting the changing social positions of women. Internal factors (health, intelligence and talent, interest and motivation, learning style) and external factors (family/parents, school/teachers, community/environment, role of family/parents) play crucial roles in students' success in the learning process. Keywords: Indonesian Feminism, Educational Psychology, Qualitative research method, Sarinah's book, Social identity